2015
DOI: 10.1039/c5ta02690c
|View full text |Cite
|
Sign up to set email alerts
|

Self-lubricating organogels (SLUGs) with exceptional syneresis-induced anti-sticking properties against viscous emulsions and ices

Abstract: “Self-lubricating organogels (SLUGs)”showing exceptional surface properties are preparedviaa crosslinking of polydimethylsiloxanes in the presence of organic liquids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
225
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(229 citation statements)
references
References 39 publications
2
225
2
Order By: Relevance
“…Liu et al 40 used an ultra-thin ($110 nm) organogel layer coated on copper, iron, silicone, and aluminum surfaces and infused with silicone oil to produce slippery selfcleaning surfaces. Urata et al 41 designed infused polydimethylsiloxane (PDMS) which could spontaneously release its liquid upon environmental changes such as a temperature decrease to À15 C or humidity increase to 60% relative humidity. These polymers were prepared as a premixed liquid-polymer system which could make it an easily applicable overcoat for other materials.…”
Section: Infused Polymersmentioning
confidence: 99%
“…Liu et al 40 used an ultra-thin ($110 nm) organogel layer coated on copper, iron, silicone, and aluminum surfaces and infused with silicone oil to produce slippery selfcleaning surfaces. Urata et al 41 designed infused polydimethylsiloxane (PDMS) which could spontaneously release its liquid upon environmental changes such as a temperature decrease to À15 C or humidity increase to 60% relative humidity. These polymers were prepared as a premixed liquid-polymer system which could make it an easily applicable overcoat for other materials.…”
Section: Infused Polymersmentioning
confidence: 99%
“…1(b)]; the resulting surface, dubbed a slippery omniphobic covalently attached liquid (SOCAL), is able to repel various liquids, including low-surface-tension alkanes [6][7][8]. Finally, a suitable lubricant oil can be added to the surface, which can be structured as is the case for slippery liquid-infused porous surfaces [9,10] or flat as is the case of lubricant-infused organogels [11,12] [ Fig. 1(c)]; any liquid can then easily be removed, as long as there is a stable intercalated lubricant layer [13][14][15][16].…”
mentioning
confidence: 99%
“…2019, 6,1900996 PDMS organogels infused with various liquids were also used for anti-icing. [130] This surface also had antisticking properties against several viscous emulsions (mayonnaise, honey, ketchup, liquid glue, and Worcester sauce) and their dry solidifications. [128] Wang et al reported a liquid-paraffin swollen PDMS organogel presenting an ultralow ice-adhesion strength of 1.7 ± 1.2 kPa (at −30 °C).…”
Section: Wwwadvancedsciencecommentioning
confidence: 97%